2005
DOI: 10.1038/nsmb995
|View full text |Cite
|
Sign up to set email alerts
|

CBP80 promotes interaction of Upf1 with Upf2 during nonsense-mediated mRNA decay in mammalian cells

Abstract: In mammalian cells, nonsense-mediated messenger RNA decay (NMD) targets newly synthesized nonsense-containing mRNA bound by the cap-binding-protein heterodimer CBP80-CBP20 and at least one exon-junction complex (EJC). An EJC includes the NMD factors Upf3 or Upf3X and Upf2, and Upf2 recruits Upf1. Once this pioneer translation initiation complex is remodeled so that CBP80-CBP20 is replaced by eukaryotic initiation factor 4E, the mRNA is no longer detectably targeted for NMD. Here, we provide evidence that CBP80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(162 citation statements)
references
References 38 publications
6
154
2
Order By: Relevance
“…Our study demonstrated a conserved role of the CBP20/80 nuclear cap binding complex and the 3' to 5' exosome complex in NMD in C. elegans and in mammalian cells (Hosoda et al, 2005;Houseley et al, 2006). CBP80 augments the efficiency of NMD by interacting with UPF1 and promoting the interaction of UPF1 and UPF2.…”
Section: Regulation Of Nmd By Various Biological Processesmentioning
confidence: 62%
See 1 more Smart Citation
“…Our study demonstrated a conserved role of the CBP20/80 nuclear cap binding complex and the 3' to 5' exosome complex in NMD in C. elegans and in mammalian cells (Hosoda et al, 2005;Houseley et al, 2006). CBP80 augments the efficiency of NMD by interacting with UPF1 and promoting the interaction of UPF1 and UPF2.…”
Section: Regulation Of Nmd By Various Biological Processesmentioning
confidence: 62%
“…Among the 83 genes that regulate the expression of gfp:: bro-1(PTC), we identified C. elegans genes whose yeast or mammalian homologs have been implicated in NMD, including eIF-1/T27F7.3, nuclear cap binding protein CBP80/ncbp-1, the exosome complex and NMD3/T25G3.3 (He and Jacobson, 1995;Cui et al, 1999;Hosoda et al, 2005;Houseley et al, 2006). Consistent with previous studies, inactivation of components of EJC did not affect the expression of gfp::bro-1(PTC).…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 99%
“…NMD in mammalian cells has been proposed to take place during the so-called pioneer round of translation, while transcripts are still bound by the nuclear CBP80/20 complex rather than by eIF4E (Ishigaki et al 2001;Lejeune et al 2002). It was also suggested that CBC might have a role in promoting the interaction of NMD factors with PTC-containing transcripts (Hosoda et al 2005). While our data do not argue against the requirement of CBC for NMD activation, we demonstrate that NMD can be elicited under conditions in which translation is independent of CBC-mediated ribosomal recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…24 The m7G-cap has earlier been shown to be critical for pre-mRNA splicing, shuttling, nonsense-mediated decay, and protein translation. 25,26 Whether defects in mRNA biogenesis play any role in mediating the pleiotrophic phenotype of Bclaf1-deficient mice requires further investigation.…”
Section: Discussionmentioning
confidence: 99%